2020
DOI: 10.3390/w12102792
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical Characteristics and Groundwater Quality Evaluation Based on Multivariate Statistical Analysis

Abstract: Hydrogeochemical research and water quality evaluation are an important part of groundwater development and management projects in Dehui City, Jilin Province, China. We collected 217 groundwater samples in the study area and used two multivariate statistical methods, hierarchical cluster analysis and principal component analysis to classify groundwater; combined graphical method, piper diagram, and Gibbs diagram to characterize groundwater chemical types and distinguish the water chemical control mechanism; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Analyses were conducted via off-axis integrated cavity output spectroscopy (OA-ICOS, DLT-100 Liquid Water Isotope Analyzer, Los Gatos Research Inc., Mountain View, CA, USA) and reported in per mil (‰). The analytical precision for δ 18 O and δ 2 H was 0.2‰ and 0.6‰, respectively.…”
Section: Groundwater Sampling Analyses and Measurementsmentioning
confidence: 93%
See 2 more Smart Citations
“…Analyses were conducted via off-axis integrated cavity output spectroscopy (OA-ICOS, DLT-100 Liquid Water Isotope Analyzer, Los Gatos Research Inc., Mountain View, CA, USA) and reported in per mil (‰). The analytical precision for δ 18 O and δ 2 H was 0.2‰ and 0.6‰, respectively.…”
Section: Groundwater Sampling Analyses and Measurementsmentioning
confidence: 93%
“…With regard to the stable isotopes, the Local Groundwater Isotope regression Line (LGIL) was compiled and plotted, along with the Global Meteoric Water Line (GMWL), Greek MWL and Thessalian MWL-as depicted in Figure 11. Isotope values of δ 2 H and δ 18 O were expressed as the difference between the measured ratios of the sample and reference divided by the measured ratio of the reference, which was in turn expressed as VSMOW values (Vienna-standard mean ocean water). The isotopic ratio of δ 18 O in the study area ranged between −9.8‰ and −6.9‰ with an average value of −8‰.…”
Section: Stable Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature studies covered the application of HCA for hydro-geochemical characteristics and groundwater quality evaluation/classification based on sampled data. For example, Chai et al and Liu et al suggested that HCA is a powerful tool for evaluating groundwater pollution and identifying groundwater hydro-geochemical characteristics in China [18,19]. Similarly, HCA has been used for groundwater classification in Southern Ghana [20]; water quality assessment in East Algeria [21]; hydro-geochemical analysis of groundwater in Iran [22] to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the distribution function and calculation of the membership degree to construct the fuzzy matrix R [22].…”
mentioning
confidence: 99%